Top income share and economic growth: linear and non-linear effects - Charpe, Matthieu (Geneva, 2017)
"This paper estimates the impact of inequality on growth, focusing on non-linearity and using top income share data that provides us with yearly observations over a long time period. A first result is that the relationship between inequality and growth is non-linear in contrast with most existing studies which focus on a linear relationship. Using panel threshold regression and panel smooth threshold regression methods, we show that the impact of inequality on growth is negative but the effect is larger when inequality is low. This result differs from existing work that stresses either a positive effect using linear estimation or a concave relationship using simple non-linearity. Lastly, heterogeneity across countries is related to the magnitude and the timing of the change in the elasticity."